Legal Analysis of The Arrangement of Wakaf Agricultural Agencies On Endowments Copyright In Perspective Legislation - Nugroho Ari Wibowo; Nurul Hidayah; Hafid Zakariya (Jurnal Cita Hukum, 2019)
AbstractIntellectual Property Rights include movable property that can be represented, one of which is Copyright. Copyright as a property of Waqf is formulated in Article 16 paragraph (2) of Undang-Undang Nomor 28 Tahun 2014 Tntang Hak Cipta (Law Number 28 of 2014 About Copyright). In the waqf, there is a transfer of rights as outlined in the form of a waqf pledge made before PPAIW (Officials Maker of the Waqf Pledge Deed) in the AIW (Deed of Waqf Pledge). The purpose of this study is to find out the implementation of a copyright waqf by the Officials Maker of the Waqf Pledge Deed and the obstacles that may arise in its implementation. The research method used in the preparation of this paper is the Normative research method, using qualitative analysis techniques. From the results of the study, it can be concluded that the implementation of copyright waqf is done the same as the waqf of other objects, namely based on Peraturan Pemerintah Nomor 42 Tahun 2006 Tentang Pelaksanaan Undang-Undang Wakaf (Government Regulation Number 42 of 2006 About Implementation of Waqf Law), by officials making deed of waqf pledges. The obstacle that appears in the implementation of the waqf copyright is the lack of knowledge/understanding of a KUA (Office of Religious Affairs) head as PPAIW (Officials Maker of the Waqf Pledge Deed) in the implementation of the Pledge of Waqf on Copyright. Another obstacle is that there are no specific regulations governing the implementation of waqf on Intellectual Property.Keyword: Waqf, Intellectual Property Rights, Copyrights, PPAIW (Officials Maker of the Waqf Pledge Deed) AbstrakHak Kekayaan Intelektual termasuk harta benda bergerak yang bisa diwakafkan, salah satunya adalah Hak Cipta. Hak Cipta sebagai harta Wakaf dirumuskan dalam Pasal 16 ayat (2) Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta. Dalam wakaf terjadi peralihan hak yang dituangkan dalam bentuk ikrar wakaf yang dibuat dihadapan Pejabat Pembuat Akta Ikrar Wakaf dalam bentuk Akta  Ikrar Wakaf (AIW). Tujuan penelitian ini adalah untuk mengetahui pelaksanaan wakaf hak cipta oleh Pejabat Pembuat Akta Ikrar Wakaf serta kendala yang mungkin muncul dalam pelaksanaannya. Metode penelitian yang digunakan dalam penyusunan skripsi ini adalah metode penelitian Normatif, dengan menggunakan teknik analisis kualitatif. Dari hasil penelitian dapat diambil kesimpulan bahwa pelaksanaan wakaf hak cipta dilakukan sama seperti wakaf benda lainnya, yaitu berdasarkan Peraturan Pemerintah Nomor 42 Tahun 2006 Tentang Pelaksanaan Wakaf yang dilaksanakan oleh Pejabat-Pembuat-Akta-Ikrar-Wakaf. Kendala yang muncul dalam pelaksanaan wakaf hak cipta adalah kurangnya pengetahuan/pemahaman seorang kepala KUA sebagai PPAIW dalam pelaksanaan Ikrar Wakaf terhadap Hak Cipta. Kendala lainnya adalah tidak ada peraturan yang khusus mengatur tentang pelaksanaan wakaf terhadap Harta Kekayaan Intelektual.Kata Kunci: Wakaf, Hak Kekayaan Intelektual, Hak Cipta, Pejabat Pembuat Akta Ikrar АннотацияПрава интеллектуальной собственности включают движимое имущество, которое может стать вакфом, одним из таких прав является Авторское право. Авторское право как имущество Вакфа сформулировано в Главе 16  пункта (2) Закона № 28 от 2014 года об Авторском праве. На Вакфе есть переход прав, описанный в форме заверения Вакфа, сделанного перед официальным представителем по созданию акта об заверении Вакфа в форме Акта об заверении Вакфа (AIW). Цель этого исследования состоит в том, чтобы определить реализацию вакфа авторского права официальным представителем по созданию акта об заверении Вакфа и препятствия, которые могут возникнуть при его реализации. Метод исследования, использованный при подготовке данной статьи, является нормативным методом исследования с использованием методов качественного анализа. Из результатов исследования можно сделать вывод, что реализация вакфа авторских прав осуществляется так же, как и вакф других объектов, а именно на основании Постановления правительства № 42 от 2006 года о реализации вакфов официальным представителем по созданию акта об заверении Вакфа. Препятствием, возникающим при реализации закона о вакфе авторского права, является недостаток знаний/понимания главы Офиса по Духовным Делам как PPAIW при реализации Заверения Вакфа по Авторскому Праву. Еще одно препятствие заключается в том, что не существует конкретного регулирования о реализации Вакфа  по объекту интеллектуальной собственности. Ключевые слова: вакф, права на интеллектуальную собственность, авторские права, официальный представитель по созданию акта об заверении Вакфа